Assessment of the effectiveness of β-adrenoceptor blocking agents towards cardiac and bronchiolar responses of the pithed guinea-pig to electrical stimulation of the spinal outflow - Burden, D. T. (1972)
1. The responses of heart rate and resistance to lung inflation of the pithed guinea-pig on electrical stimulation of the thoracic spinal roots could be related to similar responses to injected catecholamines, such that dose-stimulus frequency relations could be plotted. 2. The range of frequency of stimulation that was equi-effective with a dose range of injected catecholamines was higher for effects on air overflow than for heart rate. The slope of the relations for heart rate also differed from that for air overflow. These features may reflect a difference in effectiveness of the sympathetic innervation of heart and bronchial tree. 3. Propranolol was equally effective in reducing the responses of heart rate and air overflow to injected noradrenaline. Practolol was somewhat more active against the effects of noradrenaline on air overflow than on heart rate, though equally active against the effects of isoprenaline. 4. For the assessment of equivalent blockade of the effects of cord stimulation on heart rate and air overflow, frequency-ratios corresponding to a noradrenaline dose-ratio of 2 were derived from the slopes of the dose-frequency relations; for air overflow this value was approximately 2 and for heart rate approximately 1·4. 5. When the doses required to produce these degrees of blockade were computed from the dose-response relations for blockade of the effects of cord stimulation by propranolol, they were found to be similar for effects on heart rate and air overflow. For practolol, the effective dose for block of heart rate increase was found to be lower than that for air overflow.